Antimicrobial Efficacy of Acacia nilotica, Murraya koenigii L. Sprengel, Eucalyptus hybrid, Psidium guajava extracts and their combinations on Fusobacterium nucleatum and Porphyromonas gingivalis - B R Chandra Shekar; Ramesh Nagarajappa; Richa Jain; Rupal Singh; S Suma; Rupesh Thakur (Wolters Kluwer Medknow Publications, 2018)
Background: The herbal extracts have been effectively tried in the treatment and prevention of many oral diseases. Aim: The aim is to assess the antimicrobial efficacy of Acacia nilotica, Murraya koenigii L. Sprengel, Eucalyptus hybrid, Psidium guajava extracts and their combinations on Fusobacterium nucleatum (Fn) and Porphyromonas gingivalis (Pg). Materials and Methods: The extraction process was carried out by Soxhlet apparatus using ethanol as solvent. The combinations of the four plant extracts were prepared by combining an equal quantity of 10% solution of each of the four plant extracts. The antimicrobial efficacy testing of the plant extracts and their combinations on Fn and Pg was performed using agar well diffusion method. Columbia 5% of sheep blood agar plates were used for antimicrobial efficacy testing under anaerobic conditions. The qualitative assay was carried out to identify the various phytochemical constituents. Dimethyl sulfoxide and 0.2% chlorhexidine acted as negative and positive controls, respectively. The mean diameter of inhibition zone between different categories was compared using one-way analysis of variance. Results: All the individual plant extracts and their double, triple, and quadruple combinations were effective in inhibiting the growth of these bacteria. However, 0.2% chlorhexidine produced the highest mean diameter of inhibition zone. Conclusion: The plant extracts in combinations offer enhanced antimicrobial efficacy due to their synergistic action besides slowing the development of bacterial resistance. Hence, these extracts in combinations could be used tried as effective alternates to chlorhexidine.